Do it yourself: humic acid - Chooi, Lin Phooi; Azman, Elisa Azura; Ismail, Roslan (Universiti Putra Malaysia Press, 2022)
The humic substance consists of humic acid, fulvic acid, and humin. Humic acid is a useful metal complexing agent, a good dispersant, and a redox agent. Humic acid showed an auxin-like activity and thus promoted root growth and development. It positively affected soil’s physical, chemical, and biological properties. Hence, humic acid indirectly improved plant growth by chelating nutrients to the plant. However, humic acid converted carcinogen compounds in chlorinated water. Still, humic acid is a good compound for agricultural purposes. Humic acid can be produced in thermophilic composting, vermicomposting, and Bokashi. The humification process can occur with decomposers such as black soldier fly. Those methods can be made in farmland and even in the housing area. Extraction of humic acid is required from those production methods. However, it is not easy to extract by farmers on a small scale. Full compost and Bokashi or its tea also showed much humic acid alone. Humic acid extraction may be optional but good as crop tonic. Nonetheless, further study should be carried out. Bokashi tea and leachate with decomposer should be further studied to obtain more evidence of their benefits. With the benefit of composting and fermentation, further study on treating is required for food security.